Cicatrização de anastomoses traqueais após uso tópico de Mitomicina C em ratos - Daniel Oliveira Bonomi (2011)
The tracheal resection followed by end to end reconstruction is first choice in treating various benign and malignant diseases of the trachea. The main complications of this therapy include granuloma at the anastomotic site, suture dehiscence and stenosis, which, although uncommon, lead to high morbidity. To reduce some of these obstacles calls for the use of several drugs and wraps. The mitomycin C, an anti-cancer drug, is able to modulate wound healing by inhibiting fibroblast proliferation, thus modulating the inflammatory response. The aim of this study was to evaluate the role of hemostatic gelatin sponge soaked in mitomycin C on the healing of the trachea of rats. We used 18 male Wistar rats of similar weight and age distributed in three groups of six animals. In the control group (C), was made the devascularization of the trachea, with the aim of preventing wound healing, followed by tracheotomy, and airway reconstruction. The sponge group (E) underwent devascularization followed by tracheotomy and tracheal reconstruction, involving the anastomosis with a strip of hemostatic sponge. The group Mitomycin C (M) underwent devascularization followed by tracheotomy and tracheal reconstruction with involvement of the anastomosis by strip hemostatic sponge soaked in mitomycin C at the concentration 0.4 mg / ml. The animals were killed after fourteen days of monitoring. There was a tendency to decrease in tracheal stenosis in group M (an increase in the percentage of tracheal area), despite the higher degree of inflammation and epithelial hyperplasia, and presence of anastomotic dehiscence in two animals. It was concluded that mitomycin C may have an important role in modulating the healing of the trachea, with reduced chances of postoperative stenosis, but its acute complications prevent their indiscriminate use. Further studies with concentrations and different exposure time should be considered.